Rhodium(iii)-catalyzed C–H activation at the C4-position of indole: switchable hydroarylation and oxidative Heck-type reactions of maleimides. Issue 79 (19th September 2018) - Sherikar, Mahadev Sharanappa; Kapanaiah, Raja; Lanke, Veeranjaneyulu; Prabhu, Kandikere Ramaiah
Abstract : A Rh(iii )-catalyzed C–H activation of indole at the C4-position leading to novel and switchable functionalization has been reported by employing a weakly co-ordinating COCF3 group as a directing group. Abstract : A Rh(iii )-catalyzed C–H activation of indole at the C4-position leading to novel and switchable functionalization has been reported by employing a weakly co-ordinating COCF3 group as a directing group. An additive plays an important role in switching the selectivity between 1, 4-addition products and Heck-type products. An acid additive led to the formation of 1, 4-addition products whereas a base additive promotes the formation of Heck-type products. Deuteration studies and control experiments were helpful to propose the mechanism.